Good news, bad news : journalism ethics and the public interest - Iggers, Jeremy (Boulder, Colo. : Westview Press, 1998)
Public dissatisfaction with the news media frequently gives rise to calls for journalists to live up to the ethical standards of their profession. But what if the fault lies in part with the standards themselves?
Jeremy Iggers argues that journalism's institutionalized conversation about ethics largely evades the most important issues regarding the public interest and the civic responsibilities of the press. Changes in the ownership and organization of the news media make these issues especially timely; although journalism's ethics rest on the idea of journalism as a profession, the rise of market-driven journalism has undermined journalists' professional status.
Ultimately, argues Iggers, journalism is impossible without a public that cares about the common life. A more meaningful approach to journalism ethics must begin with a consideration of the role of the news media in a democratic society and proceed to look for practical ways in which journalism can contribute to the vitality of public life. Good News, Bad News is important reading for journalists, communication scholars, and students.
1. How Journalists Talk About Ethics -- 2. Talking in Code(s): The Foundations of Journalism Ethics -- 3. Contemporary Ethical Concepts in Historical Context -- 4. Journalism Since Cooke: The Corporate Cultural Revolution -- 5. Objectivity's Legacy -- 6. The Myth of Neutrality and the Ideology of Information -- 7. Toward a Pragmatist Ethical Theory for Journalism -- 8. Toward a Public Journalism.
Includes bibliographical references and index.
Keywords: Journalistic ethics